A robust flux splitting method with low dissipation for all‐speed flows. (12th October 2016) - Sun, Di; Yan, Chao; Qu, Feng; Du, Ruofan
Summary: In this paper, we propose a simple robust flux splitting method for all‐speed flows with low dissipation. Following the Toro‐Vazquez splitting, the inviscid flux is split into the convective and the pressure parts first. Then, we apply the Harten‐Lax‐van Leer (HLL) algorithm to each parts with low dissipation modification. Here, the modification improves the method with accurately resolving contact discontinuity and high resolution for low speed flows. Several carefully chosen numerical tests are investigated, and the results show that the proposed scheme is capable of resolving contact discontinuity, robust against the shock anomaly and accurate at all‐speeds. Because of these properties, it is expected to be widely applied to all‐speed flow studies. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We propose a robust flux splitting method with low dissipation for all speed flows. A low‐dissipation modification is properly applied to the convection and the pressure parts of the inviscid terms of the Euler equation, respectively, which improves the accuracy obviously without enhancing the computational costs of the method. The results of this study prove that the new method can enhance the accuracy and robustness for solving all‐speed flows.